State and Economy during Modern Indonesia’s Change of Regime - Jan Thomas Lindblad (Universitas Gadjah Mada, 2013)
This article serves as a general introduction to the proceedings of an international conference on ‘State and Economy in Modern Indonesia’s Change of Regimes’, held in Leiden in 2011. The article offers a synthesis of fndings in a recent research effort concerning the relationship between state and economy at the time of Indonesia’s decolonization. Findings are embedded in a wider historiographical framework and draw specifcally on the individual contributions presented at the Leiden conference. Four categories of analysis are applied concerning respectively political ecoomy, economic policy, recurrent reform and impact. The synthesis highlights the great variety of interpretations of the profund changes taking place in Indonesia at thetime of decolonization and shortly afterwards. It also demonstrates the utility of international comparison. Specifc case studies are offered concerning food policies and social medicine in Indonesia. A new vision on the transitional period known as Guided Democracy and Guided Economy is offered.